PARALEGAL EXISTENCE IN PROVIDING ACCESS TO JUSTICE FOR THE POOR IN CENTRAL JAVA - Cahya Wulandari; Sonny Saptoajie Wicaksono; Umi Faridatul Khikmah (Universitas Negeri Semarang, 2019)
The lack of Legal Aid Implementers compared to Legal Aid Recipients is expected to hamper access to justice for the poor. Therefore this research aims to provide space for Paralegals especially in the Law Faculty of UNNES to be able to provide free legal assistance outside the court of the poor in Central Java. This research will at least discuss two issues, namely 1) How is the existence of the Law Faculty UNNES Paralegal in a juridical and institutional manner in providing Legal Aid? and 2) What is the role of the Paralegal Faculty of Law at UNNES in providing Legal Aid to the poor in Central Java ?. The method used in this research is sociological juridical with a qualitative approach. The results of this study indicate that currently Paralegals can only carry out non-litigation Legal Aid. This happened because the Supreme Court based on Decision Number 22 P / HUM / 2018 had canceled the Paralegal's role in litigation. The role of Paralegals from UNNES Law Faculty students is as a facilitator or intermediary in accommodating complaints of cases and consultation from Legal Aid recipients to be conveyed to Legal Aid Providers namely lecturers who are members of the Center for Legal Aid Study, while the role of Paralegals from UNNES Law Faculty alumni is as an assistant or who helps Advocates in carrying out non-litigation Legal Assistance such as mediation, consultation, negotiation, advocating cases outside the court and making trial files. The provision of legal aid by the Paralegal is considered to be very helpful for Lecturers and Advocates in fulfilling access to justice for the poor.